1997
DOI: 10.1074/jbc.272.23.14769
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Cloning of a Broad Substrate Specificity Human Liver Carboxylesterase That Catalyzes the Hydrolysis of Cocaine and Heroin

Abstract: A human liver carboxylesterase (hCE-2) that catalyzes the hydrolysis of the benzoyl group of cocaine and the acetyl groups of 4-methylumbelliferyl acetate, heroin, and 6-monoacetylmorphine was purified from human liver. The purified enzyme exhibited a single band on SDS-polyacrylamide gel electrophoresis with a subunit mass of approximately 60 kDa. The native enzyme was monomeric. The isoelectric point of hCE-2 was approximately 4.9. Treatment with endoglycosidase H caused an increase in electrophoretic mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
3
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(190 citation statements)
references
References 47 publications
7
175
3
5
Order By: Relevance
“…Employing the carboxylesterase classification system proposed by Satoh and Hosokawa (12) this carboxylesterase belongs to the CES 2 family. It is strongly homologous with carboxylesterases AT41 (NCBI accession number BAA23605; 83% identity, 89% similarity) found in golden hamster (Mesocricetus auratus) (27) and human carboxylesterase 2 (71% identity, 82% similarity) (28).…”
Section: Discussionmentioning
confidence: 99%
“…Employing the carboxylesterase classification system proposed by Satoh and Hosokawa (12) this carboxylesterase belongs to the CES 2 family. It is strongly homologous with carboxylesterases AT41 (NCBI accession number BAA23605; 83% identity, 89% similarity) found in golden hamster (Mesocricetus auratus) (27) and human carboxylesterase 2 (71% identity, 82% similarity) (28).…”
Section: Discussionmentioning
confidence: 99%
“…In plasma, cocaine is metabolized by butylcholinesterase (pseudocholinesterase) to ecgonine methyl ester [47]. The affinity (Km) of butylcholinesterase for cocaine is approximately 11 microM, whereas the affinity of hChE1 is 116 microM [45] and the affinity of hChE2 is 390 microM [48]. The 10-fold difference in affinity suggests that at commonly encountered serum concentrations, more cocaine will be metabolized by butylcholinesterase than by hChE, and one study found that more than 50% of cocaine is metabolized by butylcholinesterase [49].…”
Section: Cocaine-protein Bindingmentioning
confidence: 99%
“…Other significant functions of the carboxylesterases include metabolism and subsequent detoxification of many agrochemicals, pharmaceuticals (Redinbo and Potter, 2005;Potter and Wadkins, 2006), metabolism of a number of therapeutics (Williams, 1985), including the cholesterol-lowering drug, lovastatin (Tang and Kalow, 1995), the antiinfluenza drug, Oseltamivir (Tamiflu) (Shi et al, 2006), the narcotic analgesic meperidine (Demerol) (Zhang et al, 1999), cocaine and heroin (Pindel et al, 1997), and resolution of racemic mixtures by transesterification, or the enantioselective hydrolysis of esters for obtaining optically pure compounds (Bornscheuer, 2002). Carboxylesterase activity is also used extensively in soft-and pro-drug design (Bodor and Buchwald, 2000, 2003.…”
Section: Introductionmentioning
confidence: 99%